Jamaica's endemic plant genera: updates in research, taxonomic knowledge, phytogeography and conservation. Issue 2 (3rd July 2018) - Commock, Tracy; Rose, Philip E.; Campbell, Keron C. St. E.; Jestrow, Brett; Francisco-Ortega, Javier
ABSTRACT: Seven plant genera are regarded as endemic to Jamaica [ Dendrocousinsia (seven species, Euphorbiaceae), Jacmaia (one species, Asteraceae), Odontocline (six species, Asteraceae), Portlandia (six species, Rubiaceae), Salpixantha (two species, Acanthaceae), Tetrasiphon (one species, Celastraceae) and Zemisia (one species, Asteraceae)]. A review pertinent to the taxonomy, distribution range, phylogenetics, conservation challenges and research updates of these genera is presented. We also provide an overview pertinent to biodiversity conservation policy and phytogeography of Jamaica. Half of the species placed in these genera have not been red-listed ( sensu IUCN), and six of them are not in situ conserved in protected areas. Tetrasiphon and D. lesteri var. glabrata have the highest conservation priority within these endemic genera. Taxonomic boundaries between species of Odontocline are poorly understood, and there is a lack of phylogenetic data for this genus. None of these endemic genera have been the subject of population biology or population genetic studies. Phytochemical research has been performed on Portlandia and the three genera of the Compositae. Among these endemic taxa only Z. discolor has been reported to have ethnobotanical usage; however, the tea infusions made from leaves of this taxon may potentially cause cirrhosis. Extracts derived from leaves of Portlandia have antitumour activity.